2004
DOI: 10.1200/jco.2004.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Relapsed Wilms’ Tumor With High-Dose Therapy and Autologous Hematopoietic Stem-Cell Rescue: The Experience at Children’s Memorial Hospital

Abstract: Our results suggest that HDT with HSCR is an effective treatment for patients with Wilms' tumor who experience relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 15 publications
2
39
0
3
Order By: Relevance
“…The introduction of these drugs into intensive chemotherapy regimens or high-dose therapy with autologous stem-cell rescue (ASCR) led to DFS rates ranging between 50 and 70% for children with recurrent WT [9][10][11][12][13][14][15].…”
Section: Filippo Spreaficomentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of these drugs into intensive chemotherapy regimens or high-dose therapy with autologous stem-cell rescue (ASCR) led to DFS rates ranging between 50 and 70% for children with recurrent WT [9][10][11][12][13][14][15].…”
Section: Filippo Spreaficomentioning
confidence: 99%
“…Trials with high-dose chemotherapy and ASCR obtained a better outcome than historical controls, with 3 or 4-year OS rates ranging from 60 to 73% [9][10][11]14,15].…”
Section: Filippo Spreaficomentioning
confidence: 99%
“…Among other things, Abu-Ghosh et al reported a good response in children treated with ICE (ifosfamide, carboplatin, etoposide) [13]. In a study by Cambell et al, after applying megachemotherapy and autologous stem cell transplant, a 4-year survival free of relapse was achieved in about 60% of the cases, and a total 4-year survival rate of 73% [14]. There was no evidence that the transplant itself was associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence risk is greater within the first 2 years after primary diagnosis (in these patients the percentage of survival approximaly ranges from 24% to 43%) but late relapses have occasionally been reported [1,10].…”
Section: Introductionmentioning
confidence: 99%